PEMBELAJARAN KREATIF MENULIS PUISI DENGAN MEDIA GAMBAR DI MI MA’ARIF NU I KALIWANGI - Muslimah (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
Writing activities are essentially not only to give birth to a thought and a feeling, but also a disclosure of knowledge ideas and the life experience of a person in writing language. The study used a qualitative approach with case study techniques. With the research subject grade V students MI ma'arif NU 1 Kaliwangi. Data collection techniques with interviews, observations, and documentation. Analytics Data uses the Miles and Huberman model. Results showed (a) mature planning before the process of dissection (b) the implementation of creative learning with the image media assisted by the LCD, and Worksheet (c) Self-reliance assessment techniques with direct observation, and system point, (d) The lack of introductory media such as dictionaries changed basic barriers.